PENGGUNAAN PROTOZOA SARCOCYSTIS SINGAPORENSIS (APICOMPLEXA: SARCOCYSTIDAE) UNTUK PENGENDALIAN TIKUS SAWAH RATTUS ARGENTIVENTER - Maryani Cyccu Tobing, Ameilia Zuliyanti Siregar, Lisnawita, dan Meirani. (Universitas Lampung, 2009)
The use of protozoan Sarcocystis singaporensis (Apicomplexa: Sarcocystidae) for control rice field rat Rattus argentiventer. Rats are still a number-one-pest in field rice of various areas in Indonesia. Biological control using microparasite Sarcocystis singaporensis (Apicomplexa: Sarcocystidae) is a highly host-specific protozoan for controlling the rats. The objective of this research was to study the use of protozoa parasite S. singaporensis against rodent pest Rattus argentiventer. The design of experiment was Factorial Randomized Complete Design with ten treatments and four replications. The first factor was sporocyt doses of S. singaporensis (control; 1 x 105; 2 x 105; 3 x 105; 4 x 105), while the second factor was rats sexual category (male and female). The results showed that dose of sporocysts S. singaporensis was significantly different but rats’ sexual category has no effect on the treatments. The highest mortalities was on dose 4 x 105 (100%) at 12.08 days, food consumption decreased two to four days before rats died, weight of rats decreased because of the infection of S. singaporensis.